(untitled) (Journal of Informatics Education and Research, 2025)
Purpose: Employee motivation and retention are essential aspects of organizational performance and competitiveness in the dynamic nature of the banking sector. This systematic review discusses critical factors that shape employee motivation and retention, concentrating on organizational culture, leadership, remuneration, and career advancement opportunities. Design/ Methodology/ Approach: A systematic review approach was used by conducting current empirical and theoretical studies concerning employee motivation and retention in banking. The review focuses on the issues of organizational culture, leadership, remuneration, career growth, and sector-specific issues such as digitalization and regulatory stresses. Findings: The findings also point to industry-specific factors, such as overwork, pressure, regulatory challenges, and the need for digitization, that require specific solutions like flexible working, upskilling, and stress management interventions. The study further points out that the expectations of the employees are divided into generations and that human resource policies should adapt to the different workforce aspirations while maintaining organizational goals. The review indicates that financial and non-financial incentives, a good work environment, and the welfare of the employees are factors that can be used to prevent turnover. Originality/ value: This study serves as a wake-up call to banking firms, suggesting an equal approach to addressing financial, personal, and professional elements of employee happiness. For further study, the regional and sectoral variation would be much more beneficial, wherein feedback from the employees would bring out more refined intervention. Organizational strategy aligned with that of employees by the banks makes sure to enhance long-term engagement and competitiveness.